Forensics - Platt, Richard; Reichs(3,(BKathys (Boston, Mass Kingfisher, 2005)
Explore the crime lab with Forensics and discover how detectives use science to solve crimes. From the scene of the crime to a criminal's conviction, discover how the marks of blood, footprints, and fingerprints can lead the police to criminals. Find out how specialists can match trace evidence, such as a single hair found on a victim, to the murderer. Learn how famous crimes were solved and,like a true detective, find out whether it was arson, poison,or murder
Signs of the crime -- The crime scene -- Collecting evidence -- Photography -- Telltale marks -- Finding a body -- Lifting prints -- Showing the invisible -- Summary -- Who is it? -- Evidence from blood -- DNA analysis -- Teeth and bones -- Making faces -- Matching fingerprints -- Unknown culprit -- Proof of guilt -- Summary -- Crime lab -- The autopsy -- How did they die? -- Trace evidence -- Dirty proof -- Computers and crime -- Bombs and fires -- Drugs and poisons -- Weapons -- Fakes and forgeries -- Summary
Includes index
11
Keywords: Criminal investigation; Forensic sciences